The novels of Maurice Gee (1962-1994) : Gee's New Zealand : in the throes of entropy : a thesis in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Lyons, Mark Robert (Massey University, 2000)
This inquiry explores the dualistic aspects of Maurice Gee's novels, particularly with reference to Prowlers and Going West. I will be highlighting the juxtaposition of opposing characters (the observers and the doers), and the opposition of mind and body - of idealism and empiricism - as developed in these two novels. I will also be investigating how Gee's novels explore the dynamics of human relationships, accounting for the recurrent themes of language, fear, death, love and madness, as they appear in his oeuvre. Chapter three explores how Gee's fiction deals with the difficulties of writing an objective account of someone's life. All these areas of investigation reveal an overall view that Gee's New Zealand society has gradually shifted towards a state of chaos and uncertainty within the last one hundred years. In chapter one I will explore the images and events, as depicted in Gee's autobiographical essay "Beginnings," that have shaped his creative imagination. I will show how they have been transformed, or re-worked, in his fiction, as well as how and why they stress the importance of imagination. I will be arguing how, through his characters, Gee continues to exorcise the traumas, conflicts and confusions of his own past, as well as demonstrating the didactic functions given to this process by his subjecting his main characters to similar experiences. I will show how Gee investigates the negative effects of a puritan heritage, and ultimately, how it can be damaging to the growing and developing adolescent psyche, causing confusion, and distorting one's perception of the real, particularly in the way it is expressed in the novel In My Father's Den. I will show how Gee's abhorrence of 'bureaucratic and institutional repression' is expressed in The Big Season, and the 'O' trilogy - at the level of community, - and in the two novels, The Special Flower and Games of Choice - at the level of family. More specifically, I will show how the narratives emphasize the need for the individual to break away from these constricting forces in order to find his own shape, and achieve a firm sense of personal identity. I will inquire into the ways in which Gee explores the idea of 'the mixed nature of the human condition' in the 'O' trilogy, and will commence a discussion of how this theme is developed in Prowlers and Going West, which will be expanded in the remaining two chapters. I will discuss how the sense of feeling 'special,' and of being in possession of 'special knowledge', can create the illusion of feeling privileged, but also how this can be seen as a burden, and how it can generate a sense of 'isolation,' thereby alienating the individual from the outside world. I will show how Gee's vision of the world can be interpreted as dualistic.
Keywords: Gee, Maurice; Criticism interpretation; Gee, Maurice. Prowlers; Gee, Maurice. Going west